Binuclear complexes of Ni(i) from 4-terphenyldithiophenol1. Issue 29 (7th August 2015) - Koch, Felix; Schubert, Hartmut; Sirsch, Peter; Berkefeld, Andreas
<x xml:space="preserve">Abstract</x> The preparation and characterisation of binuclear Ni(i) complexes from a 4-terphenyldithiophenol ligand is described.